Effect of single bout exercise modalities on multi-domain cognitive function in recreationally active older adults (efecto de modalidades de ejercicio de una sola sesión en funciones cognitivas multidominio en adultos mayores recreativamente activos) - Murshid, Syed; Linoby, Adam; Raja Hussain, Raja Nurul Jannat; Tengku Kamalden, Tengku Fadilah (Federacion Espanola de Docentes de Educacion Fisica, 2025)
Introduction: The cognitive benefits of a single session of physical activity in older adults are still being studied. Objective: This study explored the effects of single bout exercise of open-skill and closed-skill on cognitive functions, in physically active older adults. Methodology: Ninety-nine health elderly were recruited and assigned to three groups: badminton (n = 33), close skill (n = 33), and control (n=33). Cognitive assessments, such as the N-back, Stroop, and Trail Making Tests, were administered before and after the exercise sessions. Results: ANOVA showed a primary effect of group on N-back reaction time (p = 0.57), with the badminton group (812.3±25.0 ms) showing faster reaction than both the closed-skill (825±35 ms) and control groups (842.1±41.6 ms). In terms of accuracy, the badminton group (75.7±10.4%, p = 0.001) also scored higher than the control group (70.7±12.1%, p=0.001). Both exercise groups showed measurable improvements in TMT-A performance (p = 0.0002), with the badminton group (26.09±3.97s, p = 0.0001) completing the task significantly faster than the control group (32.36±5.92s, p = 0.0001). Discussion: These findings are in line with studies suggesting that open-skill exercises provide cognitive improvement than closed-skill exercise due to the nature of the exercise. Conclusions: It is suggested that open-skill exercises may offer result in immediate cognitive improvement than closed-skill activities, particularly in working memory and executive function.